2018
DOI: 10.1111/aor.13071
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical In Vitro Safety Investigations of Submicron Sized Hemoglobin Based Oxygen Carrier HbMP‐700

Abstract: Hemoglobin-based oxygen carriers (HBOCs) are being developed as oxygen and plasma volume-expanding therapeutics though their potential to promote oxidative tissue injury and nitric oxide (NO) scavenging combined with vasoconstriction has raised safety concerns. Therefore, we focused on these aspects during preclinical studies performed with the recently introduced hemoglobin microparticles (HbMP-700). Besides oxidative stress, we investigated possible vasoconstrictory influence of HBOCs as well as genetic toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…These HbOCs can induce vascular thrombosis of heart and other organs by scavenging nitric oxide rapidly leading to vasoconstriction [De Caterina et al, 1995; Lin et al, 2001; Rother et al, 2005]. Clinical trials and preclinical studies using HbOCs as artificial blood oxygen carriers have not shown significant benefits to their use especially considering the side effects [Terraneo et al, 2017; Kao et al, 2018]. Thus, careful clinical evaluation of newly developed promising strategies is required, or Hb-based carriers may be better suited for purely in vitro endeavors such as the first phases of many tissue engineering applications.…”
Section: Oxygen-delivery Approaches For Tissue Engineeringmentioning
confidence: 99%
“…These HbOCs can induce vascular thrombosis of heart and other organs by scavenging nitric oxide rapidly leading to vasoconstriction [De Caterina et al, 1995; Lin et al, 2001; Rother et al, 2005]. Clinical trials and preclinical studies using HbOCs as artificial blood oxygen carriers have not shown significant benefits to their use especially considering the side effects [Terraneo et al, 2017; Kao et al, 2018]. Thus, careful clinical evaluation of newly developed promising strategies is required, or Hb-based carriers may be better suited for purely in vitro endeavors such as the first phases of many tissue engineering applications.…”
Section: Oxygen-delivery Approaches For Tissue Engineeringmentioning
confidence: 99%
“…HBOCs may induce severe side effects and toxicity after administration, due to scavenging of vascular endothelial nitric oxide (NO) and heme-mediated oxidative reactions [38,39]. Based on our previous reports of preclinical studies, HbMPs-700 fabricated by the CCD technique are a very promising approach, demonstrating a higher affinity to oxygen, avoidance of vasoconstriction, and non-mutagenicity [22,25].…”
Section: Binding Of Haptoglobin To Surface-modified Hbmpsmentioning
confidence: 99%
“…To date, there has been a great interest in the development of HBOCs in their versatile properties, including biocompatibility, biodegradability, and low immunogenicity. Previously published data of hemoglobin particles synthesized by a co-precipitation-crosslinking-dissolution technique (CCD-technique) demonstrated HBOCs with high oxygen affinity and low immunogenicity [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Ijad Kao et al of the Charité‐Universitätsmedizin Berlin, Berlin, Germany, investigated in preclinical studies the hemoglobin‐based oxygen carrier HbMP‐700 and its potential to promote oxidative tissue injury and nitric oxide (NO) scavenging combined with vasoconstriction. This product provided a high oxygen affinity which prevented premature oxygen oversupply and avoided vasoconstriction of small blood vessels in vitro.…”
Section: Artificial Oxygen Carriersmentioning
confidence: 99%